2005
DOI: 10.1021/jp053693k
|View full text |Cite
|
Sign up to set email alerts
|

Fragility of Glass-Forming Polymer Liquids

Abstract: The fragility of polymeric glass-forming liquids is calculated as a function of molecular structural parameters from a generalized entropy theory of polymer glass-formation that combines the Adam-Gibbs (AG) model for the rate of structural relaxation with the lattice cluster theory (LCT) for polymer melt thermodynamics. Our generalized entropy theory predicts the existence of distinct high and low temperature regimes of glass-formation that are separated by a thermodynamically well-defined crossover temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
224
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 153 publications
(252 citation statements)
references
References 63 publications
26
224
1
1
Order By: Relevance
“…The generalized entropy theory has previously been applied to investigate essential molecular and physical features affecting glass-formation, [40][41][42][43][44][45] studies explain some experimentally observed trends, while many theoretical predictions are confirmed by experiments [39,40], suggesting that the theory correctly captures general trends of glass formation in polymers. We further extend the theory in this paper to investigate thermodynamic scaling of the dynamics of polymer melts, whether the LCT also predicts thermodynamic scaling, how the exponent γ varies with molecular parameters, and the relation of γ to other measurable quantities.…”
Section: A Generalized Entropy Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The generalized entropy theory has previously been applied to investigate essential molecular and physical features affecting glass-formation, [40][41][42][43][44][45] studies explain some experimentally observed trends, while many theoretical predictions are confirmed by experiments [39,40], suggesting that the theory correctly captures general trends of glass formation in polymers. We further extend the theory in this paper to investigate thermodynamic scaling of the dynamics of polymer melts, whether the LCT also predicts thermodynamic scaling, how the exponent γ varies with molecular parameters, and the relation of γ to other measurable quantities.…”
Section: A Generalized Entropy Theorymentioning
confidence: 99%
“…Moreover, some striking empirical correlations between the scaling exponent and the fragility parameter [8,12,37,38] also invite theoretical considerations. We address the above issues by employing the generalized entropy theory, [39][40][41][42][43][44][45][46] which has been previously developed to describe both the universal characteristics of glass formation and the specific properties of polymeric glass-forming liquids.…”
Section: Introductionmentioning
confidence: 99%
“…The poorer chain packing in turn can lead to an increase in the "fragility", in the context of fragile and strong glass formers. 64 Poor chain packing in fragile glass formers is known to give rise to decreases in the tensile stress at breakage, and so it is reasonable to expect that τ would decrease with increasing N as the fragility of glass formation increases. This interpretation of the trend in τ being related to the fragility of the glass-formation requires further investigation, of course, and we mention this as a tentative explanation of the trend in τ that we and others have observed.…”
Section: Calculation Of τmentioning
confidence: 99%
“…A second advance is provided by the generalized entropy theory [7][8][9][10][11][12][13][14][15] (GET), whose successes indicate directions for devising the theory. The GET formally combines a thermodynamic theory 16 for the configurational entropy of a polymer melt with Adam-Gibbs theory 17 (AGT) for the structural relaxation time τ (T).…”
Section: Introductionmentioning
confidence: 99%